2003
DOI: 10.1115/1.1537752
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Colloidal Solid Dispersions

Abstract: In the past there has been considerable interest in the possibility of using liquid lubricants containing dispersed, solid particles in the 1–50 micron size range to reduce friction and wear. These particles are used in greases and some industrial oils. Researchers are now directing their attention to the behavior of much smaller colloidal particles in the range of 5 nm to 200 nm diameter. Such systems are formally known as “colloidal sols” and have been claimed to influence friction and wear. Further reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(105 citation statements)
references
References 14 publications
0
100
0
Order By: Relevance
“…The obtained results have shown that dispersed gold nanoparticles in full-synthetic engine oil have great potential as nanolubricants since besides known good tribological properties [3] they possess a high stability at room temperature and under harsh conditions, i.e., 150°C, 6 bar, 2 h, representing real engine conditions [36]. This high colloidal stability can originate from different physicochemical aspects as discussed in the following.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results have shown that dispersed gold nanoparticles in full-synthetic engine oil have great potential as nanolubricants since besides known good tribological properties [3] they possess a high stability at room temperature and under harsh conditions, i.e., 150°C, 6 bar, 2 h, representing real engine conditions [36]. This high colloidal stability can originate from different physicochemical aspects as discussed in the following.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, permanent lubrication of combustion engines is required. Among different approaches to improve lubricants for tribological applications, metallic, e.g., Au, Bi, and Ni [1][2][3][4], and ceramic, e.g., CaCO 3 , CuO, and MOS x [5][6][7][8], nanoparticles were examined [9]. It was found that the magnitude of improvement significantly depends on nanoparticle material, size, shape, and mass concentration [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of oil additives as nanolubricants presents many advantages, as they are relatively insensitive to temperature, and tribochemical reactions are limited, compared to traditional additives. Different anti-friction and anti-wear mechanisms using the nanoparticulate additives have been explained in previous papers [10,[12][13][14]23,24].…”
Section: Introductionmentioning
confidence: 91%
“…Studies described in ref. [3][4][5] show that nanoparticle additives play the role of ball bearings between friction surfaces, resulting in decreased friction and wear. Further studies, described in [6][7][8], show that nanoparticle additives can also form a protective film over friction surfaces.…”
Section: Introductionmentioning
confidence: 99%